Nuclear ErbB-2-Induced Transcriptome Drives Triple Negative Breast Cancer Growth - Chervo, Maria F (J Endocr Soc, 2021)
Triple negative breast cancer (TNBC) refers to tumors that do not express clinically significant levels of estrogen and progesterone receptors, and lack membrane overexpression or gene amplification of ErbB-2 tyrosine kinase receptor. Transcriptome and proteome heterogeneity of TNBC poses a major challenge to precision medicine. Gene expression analyses have categorized TNBC into distinct molecular subtypes. Up to 78% of clinical TNBCs belong to the basal-like (BL) subtype. Here we found ErbB-2 in an unanticipated scenario: the nucleus of TNBC (NErbB-2). Our study on ErbB-2 alternative splicing, using a PCR-sequencing approach combined with RNA interference, revealed that BL TNBC cells express the canonical ErbB-2 (WTErbB-2), encoded by transcript 1, and the non-canonical isoform c, encoded by alternative transcript 3 (T3). The latter was not previously reported in normal or malignant cells. To characterize the isoform c we designed siRNAs targeting T3 (T3 siRNAs), which silenced up to 93% of said isoform. Transfection of T3 siRNAs into BL cells expressing only isoform c or both isoform c and WTErbB-2 was sufficient to decrease cell proliferation. Intratumoral injections of T3 siRNAs into mice bearing BL TN tumors also blocked in vivo growth. To explore whether isoform c growth-promoting effect is due to its functions as a transcriptional regulator, we performed RNA-seq in BL cells expressing only this isoform. We identified a set of genes differentially regulated in BL cells where we evicted isoform c from the nucleus, as compared to control cells. In the up-regulated group, we found enrichment of pro-apoptotic and tumor suppressor genes and in the down-regulated one, genes involved in proliferation and stemness. We used gene set enrichment analysis (GSEA) to identify the biological processes associated with these isoform c-regulated genes. We found a pronounced enrichment of gene sets related to apoptosis, activation of DNA damage pathways and cell cycle arrest in response to eviction of nuclear isoform c. GSEA also revealed negative regulation of gene sets involved in cell motility, cellular differentiation and growth pathways in BL cells lacking nuclear isoform c expression. These results suggest that NErbB-2 function modulates tumor growth and promotes a metastatic phenotype in TNBC. Furthermore, our clinical findings identified NErbB-2 as an independent predictor of shorter OS (HR 2.54; 95% CI 1.22-5.28; P = 0.013), DFS (HR 2.91; 95% CI 1.44-5.87; P = 0.003), and DMFS (HR 2.59; 95% CI 1.20-5.60; P = 0.015) in 99 TN primary tumors. Our discoveries challenge the present scenario of drug development for personalized BC medicine that focuses on wild-type proteins, which conserve the canonical domains and are located in their classical cellular compartments, highlighting the potential of NErbB-2 isoforms as novel therapeutic targets and clinical biomarkers in TNBC.